MODEL PENDIDIKAN KARAKTER QUR’ANI DI RAUDHATUL ATHFAL LABSCHOOL IIQ JAKARTA - Fafika Hikmatul Maula (el-Moona: Jurnal Ilmu Pendidikan Islam, 2019)
Character is a quality of personality that involves akhlaq and moral. It can grow naturally as people were born, and it also can be improved among family or community, which ended up being a special characteristic that differs somebody to another. The quality of someone’s personality is formed by doing basic values of character. Character is a development of character values as a base to act and work together in society. Every person has a potency that should be trained and improved. In this case, education is much epected as a main support system. However, in reality, there are many problems that cause failure in education, such as society, lack of parents’ caring, models of education, wrong methods, irrelevant materials, etc. Therefore, choosing Qur’anic character education is expected to solve the problems of people’s character values improvement nowadays.